The addition of salt in the water media containing zeolite and active charcoal on closed system transportation of gourami fish fry Osphronemus goramy Lac. - Nirmala, Kukuh; Hadiroseyani, Yani; Widiasto, Riza Purbo (Indonesian Society of Scientific Aquaculture (ISSA), 2012)
Transportation of fish fry with high density in closed system will reduce levels of O2, increasing CO2 and NH3, will also elevate the fish stress so that increase fish mortality. To reduce the effects of increased CO2 and NH3 can be applied by using zeolite and activated charcoal, while to reduce the fish stress is through the addition of salt. This study aims to determine the dose of salt added into the water containing zeolite and activated charcoal in a closed transportation system with a high fry density for 72 hours. The study was conducted two stages, namely the preliminary study and the primary study. The preliminary study involved the observation of the survival rate of fish fry during fasting, oxygen consumption rate of fish fry, the rate of total ammonia nitrogen (TAN) excretion of fish fry, and the adsorption capacity of TAN by zeolite and activated charcoal. In the primary study, fry transport simulations was carried out for 72 hours in the laboratory. Gourami fry (body length of 4 cm and body weight of 1.7 g) with the fry density of 50 fish/L were placed in the packing bag which has been filled with zeolite as much as 20 g/L and activated charcoal as much as 10 g/L. The study used a completely randomized design with five treatments and two replications: A: blank (without zeolite, activated charcoal, and salt), B: control (20 g/L zeolite+10 g/L activated charcoal), C: 20 g/L zeolite+10 g/L activated charcoal and 1 g/L salt, D: 20 g/L zeolite+10 g/L activated charcoal and 3 g/L of salt, and E: 20 g/ L zeolite+10 g/L activated charcoal and 5 g/L salt. The results of preliminary study showed that the survival rate of fish fry was 100% and active swimming for five days without food, the level of oxygen consumption as much as 1340.28 mgO2, produce NH3 as much as 22.64 mg/L, while zeolite and activated charcoal adsorbs >50% of TAN in time of 120 seconds. In the primary study, the survival rate of fish fry during the 72-hour transportation for treatments A, B, C, D, and E, were 0%, 57%, 59%, 65% and 74%, respectively. Treatment E with survival rate of 74% was obtained at NH3 concentration of 0.016±0.069 mg/L and CO2 as high as 89.89 mg/L while the DO of 4.26 mg/L. The highest growth and survival rate of fry for 17 days post-transportation was treatment E, accounting to 2.95% and 100%, respectively.Keywords: zeolite, active charcoal, closed system transportation, survival rate, gourami fish